سينوغرافية (شتاء النقود) لعقيل علي – دراسة في المشهدية الشعرية - كريم, ملكو أحمد; أحمد, كوثر كريم (Sulaimani Journal for Humanities, 2018)
The poetic language is the poet’s first tool to create scenes and images and enhance them aesthetically and visually. The modern poetic discourse has benefitted from other arts and their techniques, especially the cinema. If the cinema is a visual narrative in one of its manifestations, poetry is a written one. Aqeel Ali has benefitted from cinematic techniques in creating audio-visual scenes in his texts. In addition, he has added virtual settings and vivid portrayal of an action, a character or a situation to them. This paper is a critical analysis of the scenes depicted by the poet in his poems.